1955
DOI: 10.1071/ch9550234
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray, thermal, and Dehydration studies on Magnesium oxychlorides

Abstract: X-ray, differential thermal analysis, and dehydration methods have been used to study the magnesium oxychlorides 3Mg(OH)2.MgCl2.8H2O and 5Mg(OH)2.MgCl2.8H2O formed at temperatures below 100 �C, and 2Mg(OH), . MgCl2.5H2O and 9Mg(OH)2.MgCl2.6H2O formed at temperatures at and above 100 'C. Lower hydrates of the 3-form exist with 5 and 4 molecules of water, results which differ from those of Feitknecht and Held (1944), Feitknecht (1953), and Wehner (1933). It 1s not clear from the new results whether the lower hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
46
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…A comparison of the TG results of the present study (Table 3) with those of Cole and Demediuk [10] suggests that the foam insulation is neither a pure 3-form or 5-form magnesium oxychloride cement, or a combination of the two. In particular, the percent loss in mass of the insulation specimens in the present study was considerably less, particularly over the low temperature range, than reported by Cole and Demediuk for the magnesium oxychlorides.…”
Section: Manufacture Of Magnesium Oxychloride Cement-based Foammentioning
confidence: 88%
See 4 more Smart Citations
“…A comparison of the TG results of the present study (Table 3) with those of Cole and Demediuk [10] suggests that the foam insulation is neither a pure 3-form or 5-form magnesium oxychloride cement, or a combination of the two. In particular, the percent loss in mass of the insulation specimens in the present study was considerably less, particularly over the low temperature range, than reported by Cole and Demediuk for the magnesium oxychlorides.…”
Section: Manufacture Of Magnesium Oxychloride Cement-based Foammentioning
confidence: 88%
“…4 The results of the thermogravimetric analyses in the present study can be compared to those reported by Cole and Demediuk [10] for the 3-form and 5-form magnesium oxychloride cements. Their data (included Table 3) may be categorized into two major temperature regimes over which mass loss occurred: a low range from about 100°C (212°F) to about 175°C (347°F), and a high range of about 300 to 460°C (572 to 860°F)…”
Section: Manufacture Of Magnesium Oxychloride Cement-based Foammentioning
confidence: 89%
See 3 more Smart Citations